Integrasi Prinsip Deep Learning Dalam Implementasi Kurikulum Merdeka: Analisis Tantangan Dan Strategi Inovatif Di Pendidikan Indonesia - Ahmad Syaifulloh (PEDAGOGIA : JURNAL KEGURUAN DAN PENDIDIKAN, 2025)
The rapid advancement of deep learning over the past decade has generated significant breakthroughs across various domains, including computer vision, natural language processing, and robotics. Despite its success, several scientific gaps remain, particularly regarding robustness, interpretability, scalability, and multi-modal integration. At the same time, Indonesia is undergoing an educational transformation through the implementation of the Kurikulum Merdeka (Independent Curriculum), which emphasizes student autonomy, personalized learning, and contextualized pedagogy. Philosophically, these principles align with the notion of “deep learning” in education—learning that is mindful, meaningful, and sustainable. However, challenges such as teachers’ limited readiness, unequal infrastructure, and inconsistent implementation across schools hinder the realization of these ideals. This study employs a library research method with a qualitative descriptive approach, relying on document analysis of scholarly literature, policy documents, and empirical studies. Data analysis follows content analysis procedures to identify, categorize, and interpret themes related to deep learning’s technological and pedagogical dimensions. Findings highlight that while deep learning technologies require more robust, transparent, and resource-efficient designs, their educational parallel—deep, reflective learning—faces constraints in teacher training, assessment practices, and local contextualization. To address these challenges, the study proposes strategies for integrating deep learning principles into Kurikulum Merdeka through systematic teacher capacity-building, student-centered learning approaches, blended learning models, authentic assessment, and cross-disciplinary collaboration. Theoretically, this research contributes to the interdisciplinary discourse linking artificial intelligence and curriculum reform. Practically, it provides recommendations for enhancing teacher competencies, instructional models, and policy support to ensure that the integration of deep learning fosters effective, high-quality, and sustainable education in 21st-century Indonesia.